2004
DOI: 10.1002/cncr.20638
|View full text |Cite
|
Sign up to set email alerts
|

A renal mass in the setting of a nonrenal malignancy

Abstract: BACKGROUNDFrequently, a renal mass is identified when patients with cancer undergo studies for staging or surveillance. In determining whether it represents a metastasis, patients are frequently subjected to percutaneous renal biopsies. The authors evaluated their experience with this dilemma to formulate management guidelines.METHODSThe authors reviewed the medical records of 100 consecutive patients with nonrenal malignancies diagnosed with renal masses at presentation or follow‐up. Renal mass histology was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 54 publications
0
38
0
Order By: Relevance
“…Currently the American Urologic Association guidelines suggest renal mass biopsy when there are clinical or radiological concerns for lymphoma or metastasis to the kidney from a different solid tumour 30. In the setting of a possible non-renal malignancy, a biopsy in conjunction with molecular markers could alter management, as a renal mass may represent a metastatic site of disease nearly 20% of the time 31. In other situations, such as prior to cytoreductive nephrectomy, some experts have suggested that tissue assessment of either the primary or a distant site may be useful to help defer surgery 32.…”
Section: Discussionmentioning
confidence: 99%
“…Currently the American Urologic Association guidelines suggest renal mass biopsy when there are clinical or radiological concerns for lymphoma or metastasis to the kidney from a different solid tumour 30. In the setting of a possible non-renal malignancy, a biopsy in conjunction with molecular markers could alter management, as a renal mass may represent a metastatic site of disease nearly 20% of the time 31. In other situations, such as prior to cytoreductive nephrectomy, some experts have suggested that tissue assessment of either the primary or a distant site may be useful to help defer surgery 32.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Computed tomography (CT) is the primary diagnostic tool for renal metastases, revealing isodense masses that range from 5 to 30 Hounsfield units (HU). [3] Percutaneous renal biopsy performed on these masses provides pathological confirmation, [4] and these patients are usually treated with systemic treatment. In detected metastatic pancreatic cancer, survival can be prolonged up to 11.1 months by use of various chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Second, tissue obtained by needle biopsy does not provide sufficient pathological information. 29 Nevertheless, if there is a suspicion of metastasis originating from an other organ, 30 or preceding an ablative technique in RCC that requires a probe, needle biopsy is performed for pathological diagnosis.…”
Section: Biopsymentioning
confidence: 99%